Subsynoptic‐scale features associated with extreme surface gusts in UK extratropical cyclone events. Issue 8 (30th April 2017) - Earl, N.; Dorling, S.; Starks, M.; Finch, R.
Abstract: Numerous studies have addressed the mesoscale features within extratropical cyclones (ETCs) that are responsible for the most destructive winds, though few have utilized surface observation data, and most are based on case studies. By using a 39‐station UK surface observation network, coupled with in‐depth analysis of the causes of extreme gusts during the period 2008–2014, we show that larger‐scale features (warm and cold conveyer belts) are most commonly associated with the top 1% of UK gusts but smaller‐scale features generate the most extreme winds. The cold conveyor belt is far more destructive when joining the momentum of the ETC, rather than earlier in its trajectory, ahead of the approaching warm front. Sting jets and convective lines account for two thirds of severe surface gusts in the UK. Key Points: A novel way to quantify the relative contributions of mesoscale extratropical cyclone features is introduced Larger‐scale features are most commonly associated with the top 1% of UK surface gusts but smaller‐scale features generate the most extreme 0.1% of winds Sting jets and convective lines account for two thirds of severe surface gusts in the UK